On Global Power Differentials, Moral Realism, and the Rise of China: A Review Essay. Issue 126 (1st November 2020) - Trigkas, Vasilis
ABSTRACT: This review essay examines the recent theoretical contribution of Yan Xuetong—China's most cited political scientist—on 'Moral Realism' as it is presented in his latest magnum opus: 'Leadership and the Rise of Great Powers.' The essay evaluates the theoretical foundations of Yan's treatise as well as its application on China's domestic politics and foreign policy. Lastly the essay juxtaposes Yan's theoretical take on moral realism, which draws extensively from the Chinese pre-Qin classics, to ideas deriving from Thucydides and the Greek classics. This comparative analysis between the western and eastern strategic logic attests to the existence of a universal cannon of strategy which puts a premium on 'the first image' of analysis—that of political leadership—and acknowledges the consequentiality of utilitarian morality in global politics within the structural restrictions of the international system.